Anterior Cruciate Ligament Injury: What Are Trends in Treatment? - Zazirnyi, I.M.; Andreev, A.; Kostrub, O.O.; Kotiuk , V.V. (TERRA ORTHOPAEDICA, 2023)
Summary. There has been a reemergence of investigation into Anterior Cruciate Ligament (ACL) repair as a surgical option for patients presenting with an ACL rupture. Despite high historical failure rates, new innovations have been implemented to improve stability and biointegration in an effort to aid healing of the ligament and decrease failure rates following ACL repair. The evolution of surgical techniques has seemingly led to improved short-term outcomes over historical reports. However, there remains a paucity of literature on long-term outcomes, large series, and comparison among repair techniques. Furthermore, there have been no high-quality studies showing outcomes comparable with those after ACL reconstruction. While advancements in ACL repair have been encouraging, there are no data, to our knowledge, to support ACL repair over ACL reconstruction, as recent reports have shown high failure rates after ACL repair. For these reasons, at the present time, ACL reconstruction should remain the gold standard treatment for patients with functional impairment from an ACL rupture. In the future, there may be a role for ACL repair for select tear types in specific individuals, if the early ACL repair outcome studies produce consistent long-term outcomes comparable with those after ACL reconstruction.